METHOD OF DETERMINATION OF HEMODYNAMIC SIGNIFICANCE OF PATHOLOGICAL TORTUOSITY OF CORONARY ARTERIES - Борисюк, А. О. (Science-based technologies, 2014)
Based on the analysis of coronarograms of patients with cardiac ischemia and coronary syndrome X, a method has been developed that allows one to determine both the changes in the blood flow characteristics in the larger human coronary arteries, caused by their planar pathological tortuosity, and the hemodynamic significance of those changes proceed from the appropriate coronarography only. This method in non-invasive, allows one not to take account of a number of identical factors for the initially normal and subsequently pathologically tortuous segment of the coronary artery under investigation, and gives one the possibility to determine (with satisfactory for cardiologists precision and quickness) the required blood flow parameters at any time after carrying out the coronarography. In addition, the developed method is not associated with solving complicated technical problems, does not require special facility, special professional training and significant expences.